Discover the Legal Concept in the Sociological Study - Kadek Agus Sudiarawan; Putu Edgar Tanaya; Bagus Hermanto (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2020)
ABSTRACT This paper specifically examines the concept of law in a sociological study to find out how the law develops and how the law implemented or enforced as a unity in the legal system. This paper-based on the normative juridical method, using legal materials collected and analyzed using qualitative methods. The results show that the sociological of law studies as part of the activities of drafting legal products and the preparation of legal products is not just a juridical process. The processes of transformation from social desires into laws and regulations both in political and sociological contexts do not only occur during the formation of a regulation, continue and continually correct the legal products that produced. Law enforcement related to the sociology of law that observes the reality of how the law is working on different social structures, this scientific approach is expected to not only provide advice related to the development of legal science alone, but also must be applied, but unfortunately in the development of this science itself is not able to develop dynamically because observations that are not equally displayed in providing input to the development of legal protection in Indonesia.